KANDUNGAN NITRIT, NITRAT, DAN FOSFAT AIR SUNGAI KARANG MUMUS DARI HULU SAMPAI HILIR - Chindy Sanjaya; Vita Pramaningsih; Reni Suhelmi; Deny Kurniawan (Universitas Lambung Mangkurat, 2023)
The river found in Samarinda City is the Karang Mumus River. This river is a tributary of the Mahakam River which divides Samarinda City in East Kalimantan. The polluting source of the Karang Mumus River comes from domestic activities such as settlements, markets, shopping centers, and hotels. The purpose of this study is to determine the water quality of the Karang Mumus river in terms of predetermined parameters, namely nitrites, nitrates and phosphates in waters. This type of research is a descriptive study with a qualitative approach to see the concentration of nitrite, nitrate, and phosphate parameters in the water of the Karang Mumus River from Upstream to Downstream. The results showed that the highest nitrite value based on eight segments was in segment 3 is 0.026 mg/L. The lowest value of nitrite was in segment 8 with a concentration of 0.0095 mg/L. Based on PerDa KalTim No. 02 of 2011 class II nitrite value in all segments is still meet the quality standard of 0.06 mg/L. The highest concentration of nitrate is upstream, in segment 2 with a concentration of 0.155 mg/L. Lowest nitrate concentration is in the middle of segment 5, which is 0.069 mg/L. Based on PerDa KalTim No. 02 of 2011 class II nitrate value in all segments is still meet the quality standard of 10 mg/L. The lowest phosphate concentration in the middle of segment 5, is 0.031 mg/L. The highest phosphate concentration is upstream of segment 1, which is 0.098 mg/L. Based on PerDa KalTim No. 02 of 2011 class II, the phosphate value in all segments is still meet the quality standard of 0.2 mg/L.